Situated cognition and the ethnographic study of translation processes: Translation scholars as outsiders, consultants and passionate participants - Milošević, Jelena; Risku, Hanna (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
Whereas traditional methods of translation process research aim predominantly at fulfilling the requirements for controlled scientific experiments, shifts towards embodiment and situatedness at a conceptual level require methodological innovations for the analysis of cognitive processes as embedded in their relevant environments. In this article, we concentrate on one of the main challenges in the ethnographic study of translation processes in the translation workplace: the relationship between the researchers and the participants. Drawing on data from a multiple case study, we investigate the perceived role of the researchers and the mutual expectations of both the observers and the observed. In doing so, we examine the attitudes of translators and translation project managers towards researchers in a series of different work settings. Our results indicate that the enquirer posture imposed on the researchers by some participants corresponds with the formers’ planned methodological and epistemological approaches, as do their expected trade-offs. Others, in turn, differ substantially from the researchers in their expectations. Based on our own experience and subsequent reflections, we argue that fostering connections between translation scholars and practitioners may contribute to overcoming some of the methodological challenges of ethnographic research in Translation Studies.